ANALISIS PENAMBAHAN PENAMBAHAN CACAHAN LIMBAH MASKER MEDIS PADA KINERJA CAMPURAN ASPAL - Riyanto, sugeng (Universitas Islam Balitar Blitar, 2024)
Roads are a very important matter in the field of construction, Indonesia as a developing country that will enter into a developed country is trying to meet construction needs. Innovations related to the development of good road construction need to be implemented, so that road construction in Indonesia can run well and have results that are in accordance with the standards set in the Indonesian National Standard.In the previous research using medical mask waste, the selected part was using the inside of the mask, namely polypropylene, the results obtained were satisfactory, but it was less effective in the field directly because the mask had to be sorted inside and outside, so that for further research it was made directly. the shredded mask waste is intact, so that the manufacturing process can be carried out directly without requiring time to sort out the existing waste.The inside of a medical mask contains several polymers that are difficult to decompose, so there is a risk of contaminating the environment. Moreover, the need for masks during a pandemic is very much, and even now there is no specific way to use them optimally and safely. It is hoped that the use of medical mask waste as an asphalt mixture will increase the stability of the asphalt in the event of cracks due to the large load on the road.The results of the research showed that the effect of adding mask waste was that there was the greatest increase in stability in the 5% mixture, and gradually decreased in the 10%, 15% and 20% mixture. Compared to the normal mixture (0%) the stability value increased by 70% in the 5% mask mixture. The effect of adding a mask mixture makes the flow value smaller, so that the asphalt has insufficient flexibility. The MQ or Marshall Quotient value is largest in the 15% mixture. A mixture of 10%, 15%, 20% does not meet the VIM values determined in the 2018 general construction specifications.Kata kunci: Infrastructure, Roads, Asphalt, Mask Waste, Asphalt Performance